Streptococcal diseases of group B, its screening efficiency and role in neonatal and gynecological practice - Luguze, Linda; Abramova, Anna (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Beta-haemolytic streptococcus of group B (BGS) is one of the main reasons for perinatal morbidity and mortality in developed countries. It is one of the key initiators of early sepsis and meningitis in new-born period. BGS is the cause of neonatal death for 1 new-born per 10 000. Prospectively maternity histories and new-born development histories of the Riga Maternity House in the period from 01.07.2013 to 31.12.2013 were analyzed. All in all 712 randomly selected records were examined, children born from 37th to 42nd week of pregnancy (median 39th week of pregnancy), with a birth weight of 2100 to 4880 grams, of which 373 were girls and 339 boys. The study included both neonates, whose mothers during pregnancy were screened for streptococcus of group B, and those, whose mothers were not screened, or the result was not known at the time of birth. The data were processed and statistically analyzed using programs MS Excel and SPSS Statistics 20. Results of SPSS Statistics 20 were compared using the chi-squared test. Out of 712 pregnant women viewed, who should have been screened according to national procedure, it was done and the result at the time of birth was known for 502 pregnant women (71%). Of 502 pregnant women who were screened, a positive result, which means that a woman was a BGS carrier, was confirmed in 87 cases (17%). Intrauterine infection of new-born, whose mothers were screened positive, was found in 15 cases (17%), and new-born, whose mothers were screened negative – in 24 cases or 6%. The only sepsis risk factor found in a study group was anhydrous childbirth period that is longer than 18 hours. The number of carriers of Group B streptococcus in Latvia coincides with the average number in the world. Although the number of antenatally unobserved pregnant women in Latvia is only around 2%, Group B streptococcus screening coverage of pregnant women is limited. Even when adequate prophylactic antibiotic therapy is received, it does not fully eliminate the possibility of intrauterine infection.